2019
DOI: 10.1007/s12325-019-01117-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anal Fistulas in Europe: Systematic Literature Reviews and Population-Based Database Analysis

Abstract: Introduction: Despite the fact that perianal fistulas are associated with significant morbidity and impaired quality of life, their prevalence in Europe is unknown. The aim of this study was to estimate the prevalence of perianal fistulas in Europe, overall and according to etiology. Methods: Two independent literature reviews were performed using different search strategies to maximize the identification of potentially relevant studies. Data from relevant articles were used to estimate the prevalence of peria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 52 publications
2
27
0
6
Order By: Relevance
“…Most anal fistula patients identified in this study were idiopathic. This finding is consistent with previous studies[4,31,32] and a recently conducted systematic literature review on anal fistula prevalence[8]. As the fistula duration is longer for patients with CD than for patients without[33-36], we adjusted the look-back period for prevalence estimates accordingly, which allowed for accurate prevalence estimate.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Most anal fistula patients identified in this study were idiopathic. This finding is consistent with previous studies[4,31,32] and a recently conducted systematic literature review on anal fistula prevalence[8]. As the fistula duration is longer for patients with CD than for patients without[33-36], we adjusted the look-back period for prevalence estimates accordingly, which allowed for accurate prevalence estimate.…”
Section: Discussionsupporting
confidence: 87%
“…Reported population-based incidence estimates for anal fistula in CD patients range between 1.2%[37] to 7.5%[38]. Based on these values, a systematic review calculated anal fistula prevalence among CD patients to be 3.4%-6.0% in the Europe[8]. Our study’s prevalence estimates of anal fistula patients with CD (0.44/10000 patients, United Kingdom standardized) are not directly comparable to these results, as the denominators represent different patient populations (we used the number of total patients instead of number of CD patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 20,000 to 25,000 newly confirmed cases in the USA each year ( 1 ). A statistical analysis based on a large population database in the UK showed that the incidence of anal fistula is 1.69 cases per 10,000 individuals ( 2 ). This was also evidenced by other relevant studies ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative incidence of perianal fistulas among CD patients in the US is approximately 10% at 1 year after diagnosis, 15% at 5 years, 18% at 10 years, 23% at 20 years, and 24% at 30 years [ 2 , 4 ]. The overall prevalence of perianal fistulas in Europe, estimated as the sum of the estimated prevalence for all etiologies, was 1.69/10,000 population [ 5 ]. In a multicenter study in Korea, 35% of CD patients had a history of perianal fistula, while 28% had concomitant perianal fistulas at the time of the CD diagnosis [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%